Poor Taste and Smell Are Associated with Poor Appetite, Macronutrient Intake, and Dietary Quality but Not with Undernutrition in Older Adults - Fluitman, Kristina S (J Nutr, 2021)
BACKGROUND: Age-related declines in taste and smell function are widely assumed to contribute to the decrease in appetite and the development of undernutrition in older adults. OBJECTIVES: Here we aim to assess the associations of both taste and smell function with several nutrition-related outcomes in a single study, with poor appetite and undernutrition as primary outcomes. METHODS: This is a cross-sectional cohort study of 359 community-dwelling Dutch older adults, aged 65–93 y. Taste function was measured for all 5 basic tastes. Smell function was assessed with 3 tests: for odor identification, discrimination, and threshold. Self-reported taste and smell, appetite, energy (kcal/d) and macronutrient (% energy) intake, and covariates were assessed with extensive questionnaires. Dietary quality was calculated using the Dutch Healthy Diet index 2015, Alternative Healthy Eating Index 2010, and Mediterranean Diet Score. Body measurements included body weight (current and 2 y prior), height, and body impedance analysis. Data were analyzed via multiple logistic and linear regression. RESULTS: Of our sample, 9.2% had poor taste and 17.0% poor smell, 6.1% had poor appetite, and 21.4% were undernourished. Self-reported poor taste (OR: 8.44; 95% CI: 1.56, 45.56; P = 0.013) was associated with poor appetite, but no other taste or smell score was associated with either poor appetite or undernutrition. Some associations were found of individual taste and smell scores with macronutrient intake and dietary quality. Self-reported poor taste and smell were both consistently associated with poorer dietary quality. CONCLUSIONS: In community-dwelling older adults, specific taste and smell impairments may have diverse consequences for appetite, food intake, or dietary quality. However, this does not necessarily result in undernutrition. The consistent associations of self-reported poor taste and smell with poor dietary quality do underline the usefulness of this information when screening for nutritional risk.